Human–Autonomy Teaming: Definitions, Debates, and Directions - Lyons, Joseph B.; Sycara, Katia; Lewis, Michael; Capiola, August (Frontiers in Psychology, 2021)
Researchers are beginning to transition from studying human-automation interaction to human-autonomy teaming. This distinction has been highlighted in recent literature, and theoretical reasons why the psychological experience of humans interacting with autonomy may vary and affect subsequent collaboration outcomes are beginning to emerge (de Visser, Pak, & Shaw, 2018; Wynne & Lyons, 2018). In this review, we do a deep dive into human-autonomy teams (HATs) by explaining the differences between automation and autonomy and by reviewing the domain of human-human teaming to make inferences for HATs. We examine the domain of human-human teaming to extrapolate a few core factors that could have relevance for HATs. Notably, these factors involve critical social elements within teams that are central (as argued in this review) for HATs. We conclude by highlighting some research gaps that researchers should strive toward answering, which will ultimately facilitate a more nuanced and complete understanding of HATs in a variety of real-world contexts.